Initiation of opioid agonist treatment and subsequent substance use and other patterns among adolescents and young adults in Vancouver, Canada. (1st June 2022) - Pilarinos, Andreas; Fast, Danya; Nosova, Ekaterina; Kwa, Yandi; Joe, Ronald; Buxton, Jane A.; DeBeck, Kora
Abstract: Background: Opioid agonist treatments (OAT) are effective interventions for reducing illicit opioid use; however, less is known about OAT among adolescents and young adults (AYA). This study sought to examine OAT retention and discontinuation among AYA. Methods: Data were derived from the At-Risk Youth Study, a prospective cohort of street-involved AYA in Vancouver, Canada, between September 2005 and December 2018. Multivariable Cox regression analysis was employed to identify sociodemographic, substance use, and other factors associated with time to first OAT. Substance use, homelessness, service utilization, and criminal justice patterns among AYA who did and did not initiate OAT were examined using before and after analysis. Results: Of 676 AYA who reported weekly illicit opioid use, 454 (67.2%) reported not being on OAT at some point over the study period and 217 (32.1%) initiated OAT over follow-up. In non-linear growth curve analysis, only participants retained in OAT demonstrated significant reductions in daily illicit opioid use when compared to 'no OAT' controls (p < 0.05). Nevertheless, reductions in homelessness (p = 0.070) and increases in difficulty accessing services (p = 0.078) were observed between participants retained in OAT vs. 'no OAT' controls, while reductions in homelessness (p = 0.085) and weekly non-medical prescription opioid use (NMPOU) (p = 0.061) were observed between 'OAT discontinuers' vs. 'no OAT' controls. Conclusions: Despite finding that OAT retention was associated with significant reductions in daily illicit opioid use, no significant improvements in other key indicators were observed. This underscores the importance of providing supports alongside OAT to improve treatment outcomes among AYA. Highlights: This study examined opioid agonist treatment (OAT) outcomes among young people. OAT retention was associated with reductions in daily illicit opioid use. No other reductions, in substance use nor other outcomes, were observed. Young people who use opioids require a continuum of health and social supports.